ANALISIS AKUNTANSI PENGAKUAN PENDAPATAN DAN BEBAN PADA PT. PROPERTY GROUP IMPERIUM MEDAN - Rudyanto Simanjuntak; Santi Koeswara; Sunarji Harahap; Elidawati (JURNAL BISNIS KOLEGA, 2019)
Abstract. The purpose of this study is to Accounting Analysis of Revenue Expense on PT. Property Group Imperium Medan, analysis Expense on PT. Property Group Imperium Medan and PT. Property Group Imperium Medan This research uses descriptive method, namely the method of analyzing the problem by collecting data and grouping it in a sequence to describe each process, as well as the behavior of the object under study at PT. Property Group Imperium Medan so that it can provide objective information and information. The results of this study indicate that accounting for revenue recognition on PT. Property Group Imperium Medan was declared to be still incompatible with clear reporting transactions and in the principles and methods of sales in the calculation. Keywords: Accounting for Revenue Recognition, Expenses